Purification and Characterization of Endoglucanase from local isolate of Aspergillus flavus (Baghdad Science Journal, 2025)
Endoglucanase produced from Aspergillus flavus was purified by several steps including precipitation with 25 % ammonium sulphate followed by Ion –exchange chromatography, the obtained specific activity was 377.35 U/ mg protein, with a yield of 51.32 % .This step was followed by gel filtration chromatography (Sepharose -6B), when a value of specific activity was 400 U/ mg protein, with a yield of 48 %. Certain properties of this purified enzyme were investigated, the optimum pH of activity was 7 and the pH of its stability was 4.5, while the temperature stability was 40 °C for 60 min. The enzyme retained 100% of its original activity after incubation at 40 °C for 60 min; the optimum temperature for enzyme activity was 40 °C.